Burrowing Behavior of a Deposit Feeding Bivalve Predicts Change in Intertidal Ecosystem State - Compton, Tanya J.; Bodnar, Wanda; Koolhaas, Anita; Dekinga, Anne; Holthuijsen, Sander; ten Horn, Job; McSweeney, Niamh; van Gils, Jan A.; Piersma, Theunis (Frontiers in Ecology and Evolution, 2016)
Behavior has a predictive power that is often underutilized as a tool for signaling ecological change. The burrowing behavior of the deposit feeding bivalve Macoma balthica reflects a typical food-safety trade-off. The choice to live close to the sediment surface comes at a risk of predation and is a decision made when predation danger, food intake rates or future fitness prospects are low. In parts of the Dutch Wadden Sea, Macoma populations declined by 90% in the late 1990s, in parallel with large-scale mechanical cockle-dredging activities. During this decline, the burrowing depth of Macoma became shallow and was correlated with the population decline in the following year, indicating that it forecasted population change. Recently, there has been a series of large recruitment events in Macoma. According to the food-safety trade-off, we expected that Macoma should now live deeper, and have a higher body condition in association with this change in depth of living. Indeed, we observed that Macoma now lives deeper and that living depth in a given year forecasted population growth to the next year, especially in individuals larger than 14 mm. As living depth and body condition were strongly correlated in individuals larger than 14 mm, larger Macoma could be living deeper to protect their reproductive assets. Our results confirmed that burrowing depth signals impending population change and, together with body condition, can provide an early warning signal of ecological change. We suggest that population recovery is being driven by improved intertidal habitat quality in the Dutch Wadden Sea, rather than by the proposed climate-change related effects. This shift in ecosystem state is suggested to include the recovery of diatom habitat in the top layer of the sediment after cockle-dredging ended.